Religion, ethnicity and xenophobia in the Bible - Rainey, Brian, author.
1 online resource.
Keywords: "Religion, Ethnicity and Xenophobia in the Bible looks at some of the Bible's most hostile and violent anti-foreigner texts and raises critical questions about how students of the Bible and ancient Near East should grapple with "ethnicity" and "foreignness" conceptually, hermeneutically and theologically. The author uses insights from social psychology, cognitive psychology, anthropology, sociology, and ethnic studies to develop his own perspective on ethnicity and foreignness. Starting with legends about Mesopotamian kings from the third millennium BCE, then navigating the Deuteronomistic and Holiness traditions of the Hebrew Bible, and finally turning to Deuterocanonicals and the Apostle Paul, the book assesses the diverse and often inconsistent portrayals of foreigners in these ancient texts. This examination of the negative portrayal of foreigners in biblical and Mesopotamian texts also leads to a broader discussion about how to theorize ethnicity in biblical studies, ancient studies and the humanities. This volume will be invaluable to students of ethnicity and society in the Bible, at all levels"--